Lean manufacturing practices, corporate social responsibility and sustainability performance: An empirical study on Tunisian manufacturing companies - Lajnef, Marwa; Lakhal, Lassaad (Edelweiss Applied Science and Technology, 2025)
Given the significant contribution of manufacturing sectors to major environmental issues worldwide and the growing attention directed toward manufacturing SMEs in developing countries, this study investigates the impact of lean manufacturing practices (LMPs) on corporate social responsibility (CSR) activities and corporate sustainability performance (CSP) within manufacturing SMEs in Tunisia. We employed a survey questionnaire to collect data from managers and professionals working in 256 manufacturing SMEs and used Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data. Moreover, we examined the role played by these practices in fostering corporate sustainability. We also examined the links between LMPs, CSR activities, and CSP, considering CSR as a mediating factor between LMPs and CSP. Our findings indicate that LMPs enhance CSP both directly and indirectly through CSR practices. LMPs positively affect CSR activities within manufacturing SMEs in Tunisia. This investigation contributes to the limited body of literature on LMPs, CSR, and CSP and serves as a valuable resource for practitioners. This study provides Tunisian managers and policymakers with valuable insights to better address sustainability challenges.